Layanan Konseling Individu Pada Pecandu Narkoba di Lembaga Pemasyarakatan Kelas II A Pekanbaru - Syafitri, Fadila; Rahmad, Rahmad (Al-Ittizaan: Jurnal Bimbingan Konseling Islam, 2023)
The rampant use of drugs in Indonesia is common in various groups of teenagers and adults, so that many prison inmates are people who are affected by drug cases, which makes them physically and psychologically disturbed, so the role of counselors is needed to be able to help and guide clients who are drug addicts to make them become addicts. better. This research aims to determine individual counseling services for drug addicts in the Class IIA Pekanbaru correctional institution. This research uses a qualitative method with a descriptive approach used in this research, with data collection techniques through observation, interviews and documentation. The research results show that individual counseling services for drug addicts are carried out once a week for 15-20 minutes per person, and after they carry out this individual counseling service it can make them become better personalities than before when using drugs and become closer to their family.